Secondary prophylaxis of hepatocellular carcinoma: the comparison of direct‐acting antivirals with pegylated interferon and untreated cohort. Issue 1 (1st December 2016) - Vukotic, R.; Di Donato, R.; Conti, F.; Scuteri, A.; Serra, C.; Andreone, P.
Summary: During the past two decades, several studies showed reduced rates of hepatocellular carcinoma recurrence in patients with HCV‐related cirrhosis after interferon‐based antiviral therapies respect to untreated controls, even without reaching viral clearance. The recent development of new all‐oral regimens with direct‐acting antivirals has radically improved the therapeutic management of hepatitis C. Nevertheless, paradoxical, or at least unexpected, high rates of both occurrence and recurrence of hepatocellular carcinoma after a treatment with direct‐acting antivirals, have been reported in the recent literature. These findings generated a strong rebound in the hepatology community and are at present still controversial. We sought to compare the hepatocellular carcinoma recurrence‐free survival of a historical cohort treated with pegylated interferon/ribavirin and an untreated cohort with a cohort treated with direct‐acting antivirals.